Epoxy resin and curable resin composition
By incorporating a rigid skeleton and dimethylsilyl group into the epoxy resin structure, the issues of brittleness and processability are addressed, resulting in a curable resin composition with enhanced fluidity and mechanical properties for industrial applications.
Patent Information
- Application Number
- JP2023203782
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-07
- Filing Date
- 2023-12-01
- Publication Date
- 2025-01-21
AI Technical Summary
Epoxy resins exhibit brittleness due to microgel formation during curing, leading to insufficient mechanical strength and adhesive strength, and high-molecular-weight epoxy resins have poor processability and reduced crosslinking density, limiting their use.
Introduce a rigid skeleton and dimethylsilyl group into the epoxy resin structure to reduce viscosity and inhibit microgel formation, while maintaining a number average molecular weight of 500 or more, allowing for a curable resin composition with improved fluidity and processability.
The modified epoxy resin composition achieves good processability, mechanical strength, and adhesive properties, with low curing shrinkage and high thermal stability, suitable for various industrial applications.
Smart Images

Figure 2025010462000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an epoxy resin and a curable resin composition. [Background technology]
[0002] Epoxy resins have excellent heat resistance and mechanical properties and are therefore widely used as materials in the electrical and electronics fields, the automotive field, and various other industrial materials fields.
[0003] However, epoxy resins are generally considered to have a problem that needs to be improved due to their brittleness, and as a result, their mechanical strength, adhesive strength, and the like may not be sufficient, and therefore their use may be restricted. It is known that one of the causes of the brittleness of epoxy resins is that tiny solid particles called microgels separate from the liquid reaction system at a relatively early stage of the curing process, causing the resin to become heterogeneous (for example, see Non-Patent Document 1). It is known that the reason for the formation of the microgel is that a polymerizing reaction in which the molecular chains grow linearly during the curing stage of the epoxy resin and a branching reaction that contributes to crosslinking proceed in parallel. As a technique for suppressing the generation of such microgels, a technique has been proposed in which a pre-polymerized epoxy resin is used as a starting material in the curing process (see, for example, Patent Document 1). However, the high molecular weight epoxy resin has a high viscosity and is therefore poor in processability. Furthermore, when such a high molecular weight epoxy resin is used as a starting material in a curing process, the crosslink density of the cured product is reduced, resulting in new problems such as low heat resistance and high water absorption, which limits the range of applications.
[0004] On the other hand, it is known that the introduction of a rigid structure, such as a biphenyl structure, into the skeleton of an epoxy resin increases the heat resistance of the cured product (see, for example, Patent Document 2). In view of this, attempts have been made to oligomerize an epoxy resin by reacting an epoxy resin having a rigid structure such as a biphenyl structure with a bifunctional phenol skeleton of a different skeleton in advance. However, even in this case, there is a problem that the effect of suppressing the decrease in heat resistance is only limited. In addition, since the melting point of the epoxy resin is high, at 100°C or higher, due to the biphenyl structure, the reaction proceeds during mixing with the curing agent, deteriorating the fluidity and giving rise to new problems regarding processability (see, for example, Patent Document 3). Furthermore, epoxy resins have been reported in which aliphatic hydrocarbons have been further introduced into epoxy resins having rigid structures introduced therein (see, for example, Non-Patent Document 2). However, such epoxy resins have problems in that the synthesis of the epoxy resins is extremely difficult due to the high melting point of the phenol used as a raw material, and the aliphatic hydrocarbons that can be introduced into the epoxy resins are limited to mixtures of long chains and different aliphatic chain lengths, resulting in a significant decrease in the Tg of the cured product, making them unsuitable for practical use from the standpoints of resin productivity and heat resistance of the cured product. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO 2021 / 79812 [Patent Document 2] Japanese Patent Application Publication No. 60-67475 [Patent Document 3] Japanese Patent Application Publication No. 9-227653 [Non-patent literature]
[0006] [Non-Patent Document 1] ACS Appl. Mater. Interfaces, 4, 564-572, (2012) [Non-Patent Document 2] Journal of Polymer Science Part A, Vol. 30, 1831-1843 (1992) Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to provide an epoxy resin that exhibits fluidity and good processability that enables the preparation of a curable resin composition blended with a curing agent, etc., and a curable resin composition containing the epoxy resin. [Means for solving the problem]
[0008] Means for Solving the Problems of the Prior Art The present inventors have conducted intensive studies in order to solve the problems of the prior art described above, and as a result have found that the problems of the prior art described above can be solved by introducing a rigid skeleton and a dimethylsilyl group, which has an effect of reducing viscosity, into an epoxy resin skeleton, and by carrying out oligomerization with a design that does not contain a hydroxyl group, thereby completing the present invention. That is, the present invention is as follows.
[0009] [1] An epoxy resin represented by the following formula (1), in which B1 has a structure represented by the following formula (6) or (7), and has a number average molecular weight of 500 or more.
[0010] [ka]
[0011] In formula (1), m is a real number greater than 0, p is an integer of 0 to 5, q is an integer of 2 to 7, each R0 is independently a hydrocarbon group having 1 to 4 carbon atoms or a phenyl group, and A1 in formula (1) is a structure selected from any of the following formulae (2) to (5).
[0012] [ka]
[0013] In formula (2), A2 represents any one selected from the group consisting of a direct bond, a -COO- group, and a -CO- group; each R1 independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; each m1 independently represents an integer of 0 to 4.
[0014] [ka]
[0015] In formula (3), R1's each independently represent a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, and m1's each independently represent an integer of 0 to 4.
[0016] [ka]
[0017] In formula (4), R2's each independently represent a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, and m2's each independently represent an integer of 0 to 4.
[0018] [ka]
[0019] In formula (5), R2 and R3 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, m2 each independently represent an integer of 0 to 3, and m3 each independently represent an integer of 0 to 2.
[0020] [ka]
[0021] In formula (6), B2 represents a direct bond or an --O-- group; R1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; and m1 each independently represents an integer of 0 to 4.
[0022] [ka]
[0023] In formula (7), R1's each independently represent a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, and m1's each independently represent an integer of 0 to 4.
[0024] [2] In the formula (1), A1 is any one of the following structures: The epoxy resin described in [1] above.
[0025] [ka]
[0026] [3] In the formula (1), B1 is any one of the following structures: The epoxy resin according to [1] or [2] above.
[0027] [ka]
[0028] [4] A curable resin composition comprising the following components (A) and (B): (A): The epoxy resin according to any one of the above [1] to [3] (B): Hardener [5] (C): Further containing a curing accelerator; The curable resin composition according to [4] above. [6] The component (B) is an anionic curing catalyst. The curable resin composition according to [4] or [5] above. [7] The component (B) is a bifunctional phenol. The curable resin composition according to [4] or [5] above. [8] The component (C) is an imidazole. The curable resin composition according to any one of [5] to [7] above. [9] The component (C) is a phosphorus-based compound. The curable resin composition according to any one of [5] to [7] above. Effect of the Invention
[0029] According to the present invention, an epoxy resin is obtained which exhibits flowability that enables the preparation of a curable resin composition containing a curing agent and the like, and has good processability. [Brief description of the drawings]
[0030] [Figure 1] 1 shows the results of NMR measurement of the epoxy resin of Example 1. [Diagram 2] 1 shows the molecular weight distribution of the epoxy resin of Example 1 measured by GPC. [Diagram 3] 1 shows an exothermic curve of epoxy resin composition A of Application Example 1 measured by DSC. [Figure 4] 1 shows a DSC chart of a cured product A of the epoxy resin composition of Application Example 1. [Diagram 5] 1 shows a TMA chart of cured product A of the epoxy resin composition of Application Example 1. [Figure 6] 1 shows an exothermic curve of epoxy resin composition B of Application Example 2 measured by DSC. [Figure 7] 1 shows a DSC chart of the cured product B1 of the epoxy resin composition of Application Example 2. [Figure 8] 1 shows a DSC chart of the cured product B2 of the epoxy resin composition of Application Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and the present invention is not limited to this embodiment, and the present invention can be practiced by appropriately modifying it within the scope of its gist.
[0032] [Epoxy resin] The epoxy resin of the present embodiment is represented by the following formula (1). In the following formula (1), B1 has a structure represented by the following formula (6) or (7), and is an epoxy resin having a number average molecular weight of 500 or more.
[0033] [ka]
[0034] (m in formula (1)) The epoxy resin of the present embodiment may be a mixture of various components having different numbers of repeating units m, or may be an aggregate of components having the same number m. The value of m indicates a number average from the viewpoint of the structural formula showing the entire epoxy resin, is a real number greater than 0, and is uniquely specified by the number average molecular weight of the epoxy resin. The preferred range of the value of m in the formula (1) depends on the basic skeleton structure of the epoxy resin and cannot be uniquely determined, but for example, in one embodiment, assuming that the molecular weight of the partial molecular structure of A1 is 152, which corresponds to an unsubstituted biphenyl structure, and the molecular weight of the partial molecular structure of B1 is 168, which corresponds to a phenyl ether structure, all R0 are methyl groups, and all q are 0, the preferred value of m is 0.01 to 360, more preferably 0.1 to 100, even more preferably 1 to 50, and even more preferably 10 to 30. In this case, when m=360, the number average molecular weight of the epoxy resin is about 200,000. From the viewpoint of heat resistance, the smaller the value of m, the higher the heat resistance of the cured product using the epoxy resin of the present embodiment, which is preferable. On the other hand, from the viewpoint of low water absorption and low curing shrinkage, the larger the value of m, the lower the water absorption rate of the cured product using the epoxy resin of the present embodiment and the smaller the curing shrinkage during curing, which is preferable.
[0035] (p in formula (1)) In the formula (1), p is an integer of 0 to 5. The larger the value of p, the lower the viscosity of the epoxy resin of this embodiment tends to be, and the smaller the value of p, the higher the heat resistance of a cured product made using the epoxy resin of this embodiment tends to be. From this viewpoint, the value of p is preferably 1 to 3, and more preferably 1.
[0036] (q in formula (1)) In the formula (1), q is an integer of 2 to 7. The larger the value of q, the lower the viscosity of the epoxy resin of this embodiment tends to be, and the smaller the value of q, the higher the heat resistance of a cured product using the epoxy resin of this embodiment tends to be. From this viewpoint, the value of q is preferably 2 to 5, and more preferably 3.
[0037] (R0 in formula (1)) In the formula (1), each R0 is independently a hydrocarbon group having 1 to 4 carbon atoms or a phenyl group. The smaller the carbon number, the lower the viscosity of the epoxy resin of the present embodiment tends to be, and the larger the carbon number, the lower the moisture resistance of a cured product using the epoxy resin of the present embodiment tends to be. From this viewpoint, R0 is preferably a hydrocarbon group having 1 carbon atom or a phenyl group.
[0038] (A1 in formula (1)) In the formula (1), A1 is a structure selected from any one of the following formulae (2) to (5).
[0039] [ka]
[0040] In the formula (2), A2 represents any one selected from the group consisting of a direct bond, a -COO- group, and a -CO- group. Among these, A2 is preferred because it is the most chemically stable due to the direct bond, and because a cured product using the epoxy resin of this embodiment tends to exhibit a high Tg. In the formula (2), R1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. As the carbon number decreases, the Tg of the cured product using the epoxy resin of the present embodiment tends to be higher, and as the carbon number increases, the moisture absorption of the cured product using the epoxy resin of the present embodiment tends to be lower. From this viewpoint, R1 is preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 carbon atom, and even more preferably a hydrogen atom. In the formula (2), each m1 independently represents an integer of 0 to 4. The smaller the value of m1, the higher the Tg of the cured product using the epoxy resin of this embodiment, and the larger the value of m1, the lower the moisture absorption of the cured product using the epoxy resin of this embodiment, i.e., the higher the moisture resistance. From this viewpoint, m1 is preferably 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0041] [ka]
[0042] R1 and m1 in the formula (3) are the same as R1 and m1 in the formula (2), respectively.
[0043] [ka]
[0044] In the formula (4), R2 each independently represents either a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. As the carbon number decreases, the Tg of a cured product using the epoxy resin of this embodiment tends to be higher, and as the carbon number increases, the moisture absorption of a cured product using the epoxy resin of this embodiment tends to be lower. From this perspective, R2 is preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 carbon atom, and even more preferably a hydrogen atom. In the formula (4), m2 each independently represents an integer of 0 to 4. The smaller the value of m2, the higher the Tg of the cured product using the epoxy resin of this embodiment, and the larger the value of m2, the lower the moisture absorption of the cured product using the epoxy resin of this embodiment, i.e., the higher the moisture resistance. From this viewpoint, m2 is preferably 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0045] [ka]
[0046] In the formula (5), R2 and R3 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. As the carbon number decreases, the Tg of a cured product using the epoxy resin of this embodiment tends to be higher, and as the carbon number increases, the moisture absorption of a cured product using the epoxy resin of this embodiment tends to be lower. From this viewpoint, R2 is preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 carbon atom, and even more preferably a hydrogen atom. In the formula (5), m2 each independently represents an integer of 0 to 3. As the value of m2 is smaller, the Tg of the cured product using the epoxy resin of this embodiment tends to be higher, and as the value of m2 is larger, the moisture absorption of the cured product using the epoxy resin of this embodiment tends to be lower. From this viewpoint, m2 is preferably 0 to 2, more preferably 0 or 1, and even more preferably 0. In the formula (5), m3 each independently represents an integer of 0 to 2. The smaller the value of m3, the higher the Tg of the cured product using the epoxy resin of this embodiment, and the larger the value of m3, the lower the moisture absorption of the cured product using the epoxy resin of this embodiment, i.e., the higher the moisture resistance. From this viewpoint, m3 is preferably 0 or 1, and more preferably 0.
[0047] From the above viewpoint, in the formula (1), A1 preferably has any one of the following structures.
[0048] [ka]
[0049] (B1 in formula (1)) B1 in the formula (1) is a structure represented by the following formula (6) or (7).
[0050] [ka]
[0051] In the formula (6), B2 represents a direct bond or an -O- group. When B2 represents a direct bond, the Tg of a cured product using the epoxy resin of the present embodiment tends to be high, and when B2 represents an -O- group, the viscosity of the epoxy resin of the present embodiment tends to be low, and the workability and moldability at the curing stage tend to be excellent. In the formula (6), R1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. As the carbon number decreases, the Tg of a cured product using the epoxy resin of this embodiment tends to be higher, and as the carbon number increases, the moisture absorption of a cured product using the epoxy resin of this embodiment tends to be lower. From this viewpoint, R1 is preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 carbon atom, and even more preferably a hydrogen atom. In the formula (6), m1 each independently represents an integer of 0 to 4. The smaller the value of m1, the higher the Tg of the cured product using the epoxy resin of this embodiment, and the larger the value of m1, the lower the moisture absorption of the cured product using the epoxy resin of this embodiment, i.e., the higher the moisture resistance. From this viewpoint, m1 is preferably 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0052] [ka]
[0053] In the formula (7), R1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. As the carbon number decreases, the Tg of a cured product using the epoxy resin of this embodiment tends to be higher, and as the carbon number increases, the moisture absorption of a cured product using the epoxy resin of this embodiment tends to be lower. From this viewpoint, R1 is preferably a hydrogen atom or a hydrocarbon group having 1 to 2 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 carbon atom, and even more preferably a hydrogen atom. In the formula (7), m1 each independently represents an integer of 0 to 4. The smaller the value of m1, the higher the Tg of the cured product using the epoxy resin of this embodiment, and the larger the value of m1, the lower the moisture absorption of the cured product using the epoxy resin of this embodiment, i.e., the higher the moisture resistance. From this viewpoint, m1 is preferably 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0054] From the above viewpoints, in the formula (1), B1 preferably has any one of the following structures.
[0055] [ka]
[0056] (number average molecular weight) The epoxy resin of the present embodiment represented by the formula (1) has a number average molecular weight of 500 or more. By having a number average molecular weight of 500 or more, the polymerizing reaction at the curing stage proceeds sufficiently, preventing the branching reaction from proceeding before the polymerizing reaction occurs, sufficiently suppressing the formation of microgels, and preventing the cured product from becoming brittle. Furthermore, if the number average molecular weight exceeds 200,000, the viscosity may become high. The lower the number average molecular weight, the lower the viscosity and the better the workability and processability tend to be, while the higher the number average molecular weight, the smaller the cure shrinkage tends to be. From this viewpoint, the epoxy resin of this embodiment has a number average molecular weight of preferably 1,000 to 100,000, more preferably 2,000 to 60,000, even more preferably 3,000 to 30,000, and even more preferably 5,000 to 10,000.
[0057] [Method for producing epoxy resin] A method for producing the epoxy resin of this embodiment represented by the above formula (1) will be exemplified below.
[0058] (Allylation step) First, a compound represented by the following formula (8) (wherein A1 is the same as that in the above formula (1)) is reacted with allyl bromide, 4-bromo-1-butene, 5-bromo-1-pentene, or the like in the presence or absence of a solvent and in the presence of an alkali to obtain a dialkenyl ether compound represented by the following formula (9).
[0059] [ka]
[0060] [ka]
[0061] In the formula (9), A1 and p are the same as in the formula (1).
[0062] (Hydrosilylation process (sequence polymerization reaction)) Next, in the presence or absence of an organic solvent, the dialkenyl ether compound represented by the formula (9) and the SiH compound represented by the following formula (10) are subjected to a step-growth polymerization reaction by hydrosilylation in the presence or absence of a catalyst to obtain an allyl-terminated step-growth polymer represented by the following formula (11).
[0063] [ka]
[0064] In the formula (10), R0 and B1 are the same as in the formula (1).
[0065] [ka]
[0066] In the formula (11), m, p, q, R0, A1, and B1 are all the same as in the formula (1).
[0067] Examples of catalysts used in the hydrosilylation reaction include platinum, ruthenium, and rhodium catalysts. Among them, when a Karstedt catalyst is used as a platinum catalyst, the sequential polymerization tends to proceed more rapidly. Regarding the ratio of the dialkenyl ether compound to be reacted and the SiH compound represented by the above formula (10), a step-growth polymer having an allyl group terminal can be obtained by making the allyl group in excess in the molar ratio of allyl group to SiH group, and the molecular weight of the step-growth polymer produced tends to increase as the value of SiH group / allyl group in the molar ratio approaches 1.
[0068] (Epoxidation process) Next, in the presence or absence of an organic solvent, the allyl group-terminated step-growth polymer represented by the formula (11) is reacted with m-chloroperbenzoic acid (m-CPBA) to epoxidize the terminals, thereby obtaining the epoxy resin of the present embodiment represented by the formula (1). In the epoxidation reaction, an organic solvent can be used, if necessary. Examples of such organic solvents include, but are not limited to, chlorinated hydrocarbons such as methylene chloride and chloroform; hydrocarbons such as toluene and xylene; and ethers such as dioxane and tetrahydrofuran, of which methylene chloride and chloroform are preferred due to their high resin solubility.
[0069] (Catalyst removal process) If the catalyst is removed before the epoxidation reaction, the epoxidation reaction tends to proceed efficiently. Methods for removing the catalyst include, but are not limited to, a method in which a porous polystyrene-divinylbenzene copolymer such as macroporous polystylene-2,4,6-trimercaptotriazine is dispersed in an organic solution in which an allyl-terminated step-growth polymer is dissolved, followed by stirring, followed by filtration and distillation of the solvent.
[0070] (Coexistence of buffer solution) In addition, when an alkaline buffer solution is present in the epoxidation reaction system, the addition reaction between the carboxylic acid generated by the reaction of the peroxide compound such as m-CPBA and the epoxy group generated by the reaction can be suppressed, and the epoxidation rate tends to be increased. Examples of such an alkaline buffer solution include a phosphate buffer solution of pH 8 and an aqueous NaHCO3 solution, and the like, with a phosphate buffer solution of pH 8 being particularly preferred.
[0071] [Curable resin composition] The curable resin composition of the present embodiment contains the following components (A) and (B). (A): Epoxy resin of this embodiment (B): Hardener
[0072] (hardening agent) The curable resin composition of the present embodiment, in which the epoxy resin (A) of the present embodiment is blended with the curing agent (B), has good fluidity and processability, and gives a cured product excellent in heat resistance, mechanical strength, adhesion, low cure shrinkage, and dimensional stability, and can more effectively achieve the objects of the present invention. Examples of the curing agent (B) include, but are not limited to, anionic curing catalysts, cationic curing catalysts, phenolic curing agents, amine curing agents, and acid anhydride curing agents.
[0073] Examples of the anionic curing catalyst include imidazoles. The imidazoles are not limited to the following, but include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 1-aminoethyl-2-methylimidazole, 1-(2-hydroxy-3-phenoxypropyl)-2-methylimidazole, 1-(2-hydroxy-3-phenoxypropyl)-2-ethyl-4-methylimidazole, 1-(2-hydroxy-3-butoxypropyl)-2-methylimidazole, and the like. Examples of imidazoles include imidazole, 1-(2-hydroxy-3-butoxypropyl)-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,4-diamino-6-[2'-methylimidozolyl-(1')]-ethyl-s-ethyl-s-triazine, and 2,4-diamino-6-[2'-methylimidozolyl-(1')]-ethyl-s-ethyl-s-triazine-isocyanuric acid adduct. The amount of the anionic curing catalyst comprising the imidazoles added is usually preferably within a range of 0.2 to 10 parts by mass per 100 parts by mass of the epoxy resin (A). These may be used alone or in combination of two or more.
[0074] Examples of the cationic curing agent include boron trifluoride, boron trifluoride-amine complexes, and aromatic sulfonium salts. The amount of the cationic curing agent added is usually preferably within a range of 0.1 to 5 parts by mass per 100 parts by mass of the epoxy resin (A). These may be used alone or in combination of two or more.
[0075] Examples of phenol-based curing agents include, but are not limited to, divalent phenols (bifunctional phenols) such as 4,4'-dihydroxybiphenyl, 3,3',5,5'-tetramethylbiphenyl-4,4'-diol, bisphenol A, tetramethylbisphenol A, tetramethylbisphenol F, bisphenol S, bisphenol F, 4,4'-dihydroxydiphenyl ether, 1,6-naphthalenediol, 2,6-naphthalenediol, 2,7-naphthalenediol, 1,7-naphthalenediol, hydroquinone, and resorcin; and trivalent or higher phenols such as tris-(4-hydroxyphenyl)ethane, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, phenol novolac, and o-cresol novolac. Among these, the use of dihydric phenols is preferred because they tend to give cured products with high toughness, and among these, the use of 3,3',5,5'-tetramethylbiphenyl-4,4'-diol is preferred because they tend to give cured products with high heat resistance. The amount of the phenol-based curing agent added is usually preferably 0.5 to 1.5 equivalents, more preferably 0.8 to 1.2 equivalents, in terms of the number of moles of hydroxyl groups relative to the number of moles of epoxy groups contained in the epoxy resin (A). These may be used alone or in combination of two or more.
[0076] Examples of the amine-based curing agent include, but are not limited to, aliphatic amines such as ethylenediamine and triethylenetetramine, aromatic amines such as m-xylylenediamine, p-xylylenediamine, 2,4-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane and 4,4'-diaminodiphenylsulfone, and further allylated aromatic amines such as monoallyldiaminodiphenylmethane and diallyldiaminodiphenylmethane. As the amine-based curing agent, aromatic amines whose reaction proceeds at relatively high temperatures are preferred, and the use of 4,4'-diaminodiphenylsulfone is preferred because it tends to give a cured product with high heat resistance. The amount of the amine curing agent added is usually preferably 0.5 to 1.5 equivalents, more preferably 0.8 to 1.2 equivalents, in terms of the number of moles of active hydrogen contained in the amine relative to the number of moles of epoxy groups contained in the epoxy resin (A). These may be used alone or in combination of two or more.
[0077] Examples of the acid anhydride curing agent include, but are not limited to, dodecenyl succinic anhydride, polyadipic anhydride, polyazelaic anhydride, polysebacic anhydride, poly(ethyloctadecanedioic) anhydride, poly(phenylhexadecanedioic) anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylhimic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylcyclohexene dicarboxylic anhydride, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bistrimellitate, HET anhydride, and tetrahydrophthalic anhydride. As the acid anhydride-based curing agent, one that has a low viscosity and can provide excellent heat resistance in the cured product of the curable resin composition of the present embodiment is preferred, and from this viewpoint, hexahydrophthalic anhydride and methyltetrahydrophthalic anhydride are more preferred.
[0078] Among the above-mentioned curing agents, anionic curing agents tend to give a cured product with high heat resistance, and phenolic curing agents tend to give a cured product with excellent toughness, and therefore can be preferably used. The amount added is usually within a range of 0.5 to 1.5 equivalents, more preferably 0.8 to 1.2 equivalents, in terms of the number of moles of the acid anhydride skeleton relative to the number of moles of the epoxy groups contained in the epoxy resin (A). These may be used alone or in combination of two or more.
[0079] ((C): Curing accelerator) The curable resin composition of the present embodiment may further contain a curing accelerator (hereinafter, may be referred to as curing accelerator (C) or component (C)). By including the curing accelerator (C), the curing reaction is accelerated, and a cured product having excellent heat resistance, mechanical strength and adhesiveness can be obtained, which tends to more significantly achieve the object of the present invention. Examples of the curing accelerator (C) include, but are not limited to, imidazoles and phosphorus compounds. Specific examples of the curing accelerator include organic phosphines such as triphenylphosphine, trimethylphosphine, benzyltriphenylphosphonium bromide, amyltriphenylphosphonium bromide, benzyltriphenylphosphonium iodide, triphenylphosphonium iodide, tributylphosphine, methyldiphenylphosphine, diphenylphosphine, and phenylphosphine; tetra-substituted phosphonium and tetra-substituted borates such as tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium ethyltriphenylborate, and tetrabutylphosphonium tetrabutylborate; tetraphenylboron salts such as 2-ethyl-4-methylimidazole tetraphenylborate and N-methylmorpholine tetraphenylborate; and the compounds shown as anionic curing catalysts. The amount of the curing accelerator (C) added is usually preferably within a range of 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 1 to 5 parts by mass, per 100 parts by mass of the epoxy resin (A). These may be used alone or in combination of two or more.
[0080] [Method for producing curable resin composition] The curable resin composition of the present embodiment can be produced by mixing and kneading the above-mentioned components and then degassing under reduced pressure in accordance with a conventional method. The mixing and kneading method is not particularly limited, but examples thereof include methods using a reactor with stirring blades, a planetary mixer, a kneader, a roll, a homodisper, an extruder, and the like. The mixing and kneading step is carried out at room temperature or heated. The kneading temperature varies depending on the viscosity and melting temperature of the epoxy resin (A), but is usually preferably 25 to 250°C, more preferably 50 to 220°C, and even more preferably 100 to 180°C. If the kneading temperature is too high, exceeding 250° C., the curing reaction proceeds during kneading, and the viscosity of the obtained curable resin composition tends to increase. If the kneading temperature is too low, below 25° C., the viscosity of the epoxy resin or curing agent increases, making kneading difficult, and moisture in the air adheres to the curable resin composition, which vaporizes during curing, tending to generate voids in the cured product.
[0081] [Cured product] By curing the epoxy resin and the curable resin composition of the present embodiment, a cured product is obtained. The curing conditions are not particularly limited, but a preferred method is to react at a relatively low temperature in the initial stage until the curable resin composition gels and loses fluidity, and then to post-cure at an increased reaction temperature. That is, a preferred method is to react at a temperature of 70°C to 200°C, preferably 100°C to 180°C, more preferably 120°C to 150°C, for 20 minutes to 2 hours, preferably 40 minutes to 1.5 hours in the initial stage, and then to post-cure at a temperature higher than the initial reaction temperature and not higher than 320°C, preferably not higher than 280°C, more preferably not higher than 250°C. Furthermore, it is more preferable to carry out the above-mentioned curing step in a nitrogen atmosphere or under vacuum, since this tends to suppress oxidative deterioration.
[0082] [Other ingredients and additives] The epoxy resin and the curable resin composition of the present embodiment may contain an organic solvent, an inorganic filler, and other additives, as necessary. (Organic solvent) Examples of organic solvents include, but are not limited to, inert solvents such as xylene, toluene, N-dimethylformamide, N,N-diethylformamide, N-methyl-2-pyrrolidone, chloroform, methylene chloride, dimethylsulfoxide, dimethylphosphoramide, methyl ethyl ketone, methyl cellosolve, methyl isobutyl ketone, tetrahydrofuran, and dioxane, and toluene and N-dimethylformamide are preferred because they have a low boiling point and high volatility.
[0083] (Inorganic fillers, other additives) Examples of inorganic fillers include, but are not limited to, spherical or crushed fused silica, silica powder such as crystalline silica, alumina powder, mica, talc, calcium carbonate, alumina, hydrated alumina, asbestos, magnesium oxide, diatomaceous earth, graphite, and the like. Examples of other additives include, but are not limited to, thixotropy-imparting agents such as fine silica powder, antifoaming agents, flame retardants such as phosphorus compounds or halogen compounds, flame retardant assistants such as antimony trioxide, colorants such as carbon black and iron oxide, elastomers such as modified nitrile rubber and modified polybutadiene, release agents, leveling agents, anti-cracking agents, antifoaming agents, glass fibers, glass cloth, carbon fibers, and the like.
[0084] According to the epoxy resin of the present embodiment and the curable resin composition using the epoxy resin, it is possible to solve the problems of brittleness and adhesion caused by brittleness, and in turn to obtain a cured product that exhibits a sufficiently high Tg, moisture resistance, low water absorption, low cure shrinkage, dimensional stability, and excellent electrical properties (electrical insulation, low dielectric constant, low dielectric tangent, etc.) for practical use. EXAMPLES
[0085] Hereinafter, the present embodiment will be described in detail with reference to specific examples and comparative examples, but the present invention is not limited in any way to the following examples and comparative examples.
[0086] First, the methods for measuring and evaluating each physical property will be described below.
[0087] ((1) Number average molecular weight (Mn)) An LC-10AD manufactured by Shimadzu Corporation was used as an apparatus for measuring the number average molecular weight of an epoxy resin, and a calibration curve was prepared using standard polystyrene. Using this calibration curve, the number average molecular weight (Mn) of the epoxy resins in the examples and comparative examples described below was measured. The standard polystyrenes used were those with molecular weights of 580, 1050, 1200, 1310, 1990, 2970, 4490, 5030, 6180, 6930, 10700, 16500, 19800, 55100, 133000, 288000, 666000, 1280000, and 2780000. The column used was two Shodex LF-804 columns (manufactured by Resonac Co., Ltd.) connected in series. The solvent used was THF, the solvent flow rate was 1.0 mL / min, and the column temperature was 40°C. The detector used was a differential refractometer (RID-10A, manufactured by Shimadzu Corporation). Based on the measurement data obtained under the above conditions, the number average molecular weight (Mn) was calculated from the peak area ratio based on the curve showing the molecular weight distribution obtained by GPC.
[0088] ((2) Identification of chemical structure by NMR measurement) Regarding epoxy resin, 1 The chemical structure was identified by H-NMR measurement. Measurement equipment: Superconducting Fourier transform nuclear magnetic resonance measurement equipment (JNM-EX400 manufactured by Nippon Datum Co., Ltd.) Sample amount: Approximately 1.0 mg Measurement solvent: deuterated chloroform (CDCl3), deuterated dimethyl sulfoxide (DMSO) approx. 5 mL Internal standard: Tetramethylsilane (TMS) Magnetic strength: 400MHz Number of times: 16
[0089] ((3) Melting point measurement) The melting point of the epoxy resin was measured using a differential scanning calorimeter (DSC, SII NanoTechnology 7020) at a heating rate of 5°C / min. In this measurement, the peak temperature of the endothermic peak was taken as the melting point, and when multiple endothermic peaks existed, the endothermic peak temperature in the highest temperature region was taken as the melting point.
[0090] (4) Liquidity Assessment An epoxy resin was used as an evaluation sample, and a 50 mL eggplant-shaped flask containing 0.5 g of the sample was immersed in an oil bath at 130°C. After 20 minutes under reduced pressure of 10 mmHg or less, the fluidity of the sample was visually confirmed and evaluated.
[0091] ((5) Measurement of Tg of cured epoxy resin (DMA method) The glass transition temperature of the cured epoxy resin was measured by dynamic viscoelasticity measurement under the following conditions. The measurements were performed in a tensile mode using a non-resonant forced vibration type viscoelasticity measurement analyzer (Rheogel-E4000, manufactured by UBM). In this measurement, the peak temperature of tan δ was taken as the glass transition temperature (Tg) of the cured product. <Measurement conditions> Sample size: 30mm x 4.0mm x 0.4mm Waveform: Sine wave Frequency: 10Hz Displacement amplitude: 5μm Measurement temperature: -150~250℃ Heating rate: 2℃ / min
[0092] ((6) Water absorption rate) The epoxy resin in the cured state or before curing was used as a measurement sample. The sample was immersed in boiling water at 100° C. for 4 hours, and the mass increase rate of the sample after that was calculated to evaluate the water absorption rate. <Evaluation criteria> The smaller the mass increase, the more excellent the cured product or epoxy resin's low water absorbency was evaluated.
[0093] ((7) Adhesive strength) The curable resin composition was used as a measurement sample. The adhesive strength was evaluated by a tensile shear adhesion test in accordance with JIS K 6850:1999 (ISO 4587:1995). <Test conditions> Mild steel plate size: Length 100±0.25mm x Width 25.0±0.25mm x Thickness 1.6±0.1mm Overlap length: 12.5±0.25mm Recommended adhesive layer thickness: 0.2mm A 3.2 mm thick mild steel plate was washed with acetone and then the surface was polished with 240 grit abrasive paper. After wiping off any dirt such as polishing powder with absorbent cotton, a sample was applied to a specified area according to the above-mentioned tensile shear adhesion test, fixed with clips, and cured under specified conditions. <Evaluation criteria> The resin was evaluated as having better adhesiveness as the shear adhesive strength was higher.
[0094] ((8) Measurement of heat generation amount of curable resin composition and Tg of cured product of curable resin composition (DSC method) The calorific value of the curable resin composition before curing and the Tg (DSC method) of the cured product of the curable resin composition were measured under the following conditions using a Hitachi High-Tech Science Corporation DSC7020 differential scanning calorimeter. Sample size: 3.0 mg Measurement temperature range: 30~250℃ Heating rate: 5℃ / min
[0095] (9) Measurement of Tg of cured epoxy resin (TMA method) The glass transition temperature of the cured epoxy resin was measured by the TMA method using a mechanical analyzer TMA / SS7100 manufactured by Hitachi High-Tech Science Corporation under the following conditions. Compressive load: 10mN Measurement temperature range: -50℃~150℃ Heating rate: 5℃ / min Sample size: Length 1.0mm x diameter 4.0mm Linear expansion coefficient calculation section: -50℃~100℃ Preheat: 25℃~80℃
[0096] [Epoxy resin] Example 1 <Preparation of allyl-terminated oligomer> In a previously dried 500 mL separable flask, 13.6 g (5.12 × 10 -2 mol), 1,4-dioxane 93.2 mL, and bis[(p-dimethylsilyl)phenyl]ether 7.62 g (2.56 × 10 -2 The mixture was stirred at 90°C for 5 minutes in an oil bath until completely dissolved (under a nitrogen atmosphere, flow rate 500 mL / min). Thereto, 3.1×10 divinyltetramethyldisiloxane platinum was added as a catalyst. -2 g (Pt: 40 ppm / total resin) was added and the mixture was heated and stirred at 90°C for 2 hours (under nitrogen atmosphere: flow rate 500 mL / min). Thereafter, the solvent was removed using an evaporator at 120° C. for 0.5 hours to obtain 21.1 g of a solid (allyl-terminated oligomer) in a yield of 99%.
[0097] <Pt removal from allyl-terminated oligomers> 21.2 g of allyl-terminated oligomer and 1883 g of chloroform were placed in a 2000 mL separable flask and completely dissolved in it. 3.35 g of MP-TMT (Macroporous polystylene-2,4,6-trimercaptotriazine) was added thereto and stirred at room temperature for 1 hour. Thereafter, the MP-TMT was removed by suction filtration, and a small amount was taken out for Pt quantitative measurement, and the solvent was removed using an evaporator at 110° C. to obtain a pale yellow solid. To the remaining solution, 3.41 g of the MP-TMT was further added, and the mixture was stirred at room temperature for 1 hour, after which the MP-TMT was removed by suction filtration. The solvent was then removed using an evaporator to obtain a solid. The overall yield was 97%.
[0098] <Epoxidation> Add 4.34 g (1.04 × 10 -2 210 g of dichloromethane was added and completely dissolved. Then, 211 g of 0.1 mol / L phosphate buffer (pH 8) was added. Add 8.02 g (3.03 x 10 -2 mol) was added dropwise at 0°C or lower over 30 minutes, and the mixture was stirred at room temperature for 30 hours. Then, 5 mass % Na2SO3 aq. was added to quench the remaining m-CPBA (metachlorobenzoic acid). Thereafter, MIBK (methyl isobutyl ketone) was added, and the mixture was washed with 2.5% by mass NaHCO3 aqueous solution and 106 g / 120 g of distilled water. Thereafter, the solvent was removed using an evaporator to obtain 3.86 g (yield 88%) of epoxy resin A. The epoxidation rate of epoxy resin A was calculated from the ratio of the peak area derived from the allyl group to the peak area of the epoxy group in NMR measurement, and was found to be 83%. GPC measurement revealed that the number average molecular weight was 900. The results of NMR measurement are shown in Figure 1. The presence of glycidyl groups was confirmed from the signal at 2.8-3 ppm. The GPC measurement chart is shown in FIG. GPC measurement revealed that the number average molecular weight was 900. Since the number average molecular weight was 500 or more, it did not crystallize (had no melting point) and maintained fluidity at 130°C. It was confirmed that epoxy resin A has good fluidity under the 130°C oil bath immersion conditions described in "(4) Evaluation of fluidity" above.
[0099] [Curable resin composition and cured product] (Application Example 1) Into a previously dried 300 mL recovery flask, 2.61 g of epoxy resin A and 0.13 g of 2-phenyl-4-methyl-5-hydroxymethylimidazole were placed, and 40 g of methyl isobutyl ketone (MIBK) was further added and completely dissolved. The solvent was distilled off under vacuum for 10 minutes using a 110° C. oil bath to obtain a brown epoxy resin composition A, which is a curable resin composition. When the heat generation amount of the epoxy resin composition A was measured by DSC, a heat generation amount of 173 J / g was observed, as shown in the heat generation curve by DSC measurement in FIG. 0.36 g of the epoxy resin composition A was placed in an aluminum cup, which was then placed on a hot plate and degassed under reduced pressure at 100° C. for 15 minutes and then at 110° C. for 3 minutes. Thereafter, the mixture was placed in a thermostatic chamber and cured at 120° C. for 1 hour, then at 150° C. for 2 hours, and at 190° C. for 1 hour, to obtain a cured product A of the epoxy resin composition. Cured product A was subjected to DSC measurement and TMA measurement, and the Tg was found to be 47° C. (DSC measurement) and 44° C. (TMA measurement). FIG. 4 shows a DSC chart of the cured product A of the epoxy resin composition A, and FIG. 5 shows a TMA chart of the cured product A of the epoxy resin composition A.
[0100] [Epoxy resin] Example 2 <Preparation of allyl-terminated oligomer> In a pre-dried flask, 7.01 g (2.64 × 10 -2 mol), 50 g of 1,4-dioxane, and 7.06 g (2.37 × 10 -2 The flask was placed in an oil bath at 90°C and stirred for 5 minutes to completely dissolve the solution. To this, 2.4 × 10 divinyltetramethyldisiloxane platinum was added as a catalyst so that the amount of Pt was 50 ppm. -2 g was added, and the mixture was heated and stirred at 90°C for 3 hours (under a nitrogen atmosphere, flow rate 200 mL / min). Thereafter, the solvent was removed using an evaporator at 120° C. over 0.5 hours to obtain 13.5 g of a solid (allyl-terminated oligomer B) in a yield of 96%.
[0101] <Pt removal from allyl-terminated oligomers> 2.20 g of allyl-terminated oligomer B and 100 g of chloroform were placed in a flask and completely dissolved. 0.26 g of a metal scavenger, MP-TMT, was added thereto, and the mixture was stirred at room temperature for 1 hour. After stirring, MP-TMT was removed by suction filtration, and the solvent was removed using an evaporator at 110° C. to obtain a yellow solid (allyl group-terminated oligomer B'). The molecular weight of the allyl-terminated oligomer B' was measured by GPC, and the number average molecular weight was found to be 3,080.
[0102] <Epoxidation> In a 100 mL flask, 0.51 g (allyl group: 1.92 × 10) of the allyl-terminated oligomer B' synthesized as described above was added. -4 mol) and 15 g of chloroform were added and dissolved completely. Next, 0.59 g (2.29 × 10 -3 mol) was added dropwise at room temperature over 30 minutes, and the mixture was stirred at 50°C for 10 hours. After stirring, the reaction system was subjected to the following purification. First, 80 g of a 5% by mass aqueous solution of Na2SO3 was added, and the aqueous layer was discarded. Next, it was washed with 80 g of 2.5 mass % NaHCO3 (aqueous solution) and 70 g of distilled water. The obtained organic layer was evaporated at 130° C. for 15 minutes to remove the solvent, thereby obtaining 0.27 g of a brown solid in a yield of 52%. The obtained solid was subjected to the same procedure as above to obtain epoxy resin B. It was confirmed that epoxy resin B has good fluidity under the 130° C. oil bath immersion conditions described in “(4) Evaluation of fluidity” above.
[0103] [Curable resin composition and cured product] (Application Example 2) In a previously dried 50 mL recovery flask, 0.1 g of the epoxy resin B prepared as described above and 0.005 g of 2-phenyl-4-methyl-5-hydroxymethylimidazole were placed, and 5 g of chloroform was further added to completely dissolve them. The solvent was distilled off under vacuum for 10 minutes using a 110° C. oil bath to obtain a brown epoxy resin composition B, which is a curable resin composition. When the calorific value of the epoxy resin composition B was measured by DSC, a calorific value of 20 J / g was observed, as shown in the calorific value curve of the epoxy resin composition B by DSC measurement in FIG. 0.1 g of the epoxy resin composition B was placed in an aluminum cup, which was then placed on a hot plate and degassed under reduced pressure at 160° C. for 15 minutes. The mixture was then cured in a vacuum press at 180°C for 1 hour and then at 210°C for 1 hour to obtain a cured epoxy resin composition B1. The mixture was then cured at 230°C for an additional 1 hour to obtain a cured epoxy resin composition B2. The cured products B1 and B2 were subjected to DSC measurement and found to have Tg values of 45° C. and 57° C., respectively. The DSC charts of the cured products B1 and B2 of the epoxy resin composition B are shown in FIGS.
[0104] [Epoxy resin, resin composition] Comparative Example 1 In a 5 mL three-neck flask equipped with a stirrer and a thermometer, 300 g (1.6 mol) of 4,4-dihydroxybiphenyl, 4441 g (48 mol) of epichlorohydrin, and 3.0 g of tetramethylammonium chloride were charged and subjected to an addition reaction under heating and reflux for 2 hours. The contents were then cooled to 60°C, a moisture removal device was installed, 134.4 g (3.2 mol) of sodium hydroxide was added, and the water generated was continuously removed azeotropically at a reaction temperature of 55 to 60°C and a reduced pressure of 100 to 150 mmHg, while the epichlorohydrin layer of the distillate was returned to the reaction system to carry out a ring-closing reaction. The reaction was terminated when the amount of water produced reached 56.5 mL. Thereafter, vacuum filtration and washing with water were repeated, and further, residual epichlorohydrin was recovered by vacuum distillation. The crude glycidyl compound thus obtained was recrystallized from methyl ethyl ketone to obtain glycidyl compound A. Next, 100 parts by mass of glycidyl compound A and 20 parts by mass of bisphenol F (p-position selectivity 57%, polynuclear content 2%) were added to a separable flask and melted at 180°C, then cooled, and 1.8 mL of a 25 mmol / L NaOH methanol solution was added at 150°C, followed by reaction at 180°C for 3 hours to obtain epoxy resin a (number average molecular weight 520). It was confirmed that epoxy resin a had a structure different from that of the above formula (1). The melting point of epoxy resin a is 136°C, and it was confirmed that it had no fluidity under the 130°C oil bath immersion conditions described in "(4) Evaluation of fluidity" above. Epoxy resin A was mixed with 3 phr of 2-ethyl-4-methylimidazole and heated at 130°C, but since there was no fluidity at 130°C, a uniform resin composition could not be obtained. When the heating temperature was changed to 160°C, the curing reaction proceeded during homogenization of the resin composition, and a uniform resin composition could not be obtained. Therefore, Tg, water absorption rate, and adhesive strength could not be evaluated. [Industrial Applicability]
[0105] INDUSTRIAL APPLICABILITY The epoxy resin and curable resin composition of the present invention have industrial applicability as substrate materials for electronic components, sealants, composite materials such as CFRP and GFRP, adhesives, and paint materials.
Claims
1. Represented by the following formula (1), in which B 1 is a structure of the following formula (6) or the following formula (7), An epoxy resin with a number average molecular weight of 500 or more. 【Chemistry 1】 (In formula (1), m is a real number greater than 0, p is an integer from 0 to 5, q is an integer from 2 to 7, and R 0 are each independently a hydrocarbon group having 1 to 4 carbon atoms or a phenyl group, 1 is a structure selected from any one of the following formulas (2) to (5): 【Chemistry 2】 (A in formula (2) 2 represents any one selected from the group consisting of a direct bond, a -COO- group, and a -CO- group; R 1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; m 1 each independently represents an integer of 0 to 4.) 【Chemistry 3】 (R in formula (3) 1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; m 1 each independently represents an integer of 0 to 4. 【Chemistry 4】 (In formula (4), R 2 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; m 2 each independently represents an integer of 0 to 4. 【Chemistry 5】 (In formula (5), R 2 and R 3 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; m 2 Each independently represents an integer of 0 to 3; m 3 each independently represents an integer of 0 to 2.) 【Chemistry 6】 (In formula (6), B 2 represents a direct bond or an —O— group, R 1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; m 1 each independently represents an integer of 0 to 4.) 【Chemistry 7】 (In formula (7), R 1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms; m 1 each independently represents an integer of 0 to 4.)
2. In the formula (1), A 1 is one of the following structures: The epoxy resin according to claim 1. 【Chemistry 8】
3. In the formula (1), B 1 is one of the following structures: The epoxy resin according to claim 1. 【Chemistry 9】
4. A curable resin composition comprising the following components (A) and (B): (A): The epoxy resin according to any one of claims 1 to 3. (B): Hardener
5. (C): Further contains a curing accelerator; The curable resin composition according to claim 4.
6. The component (B) is an anionic curing catalyst. The curable resin composition according to claim 4.
7. The component (B) is a bifunctional phenol. The curable resin composition according to claim 4.
8. The component (C) is an imidazole. The curable resin composition according to claim 5 .
9. The component (C) is a phosphorus-based compound. The curable resin composition according to claim 5 .
Citation Information
Patent Citations
Purification of bishydroxybiphenyl derivative diepoxide compound
JP1985067475A
Novel epoxy resin and epoxy resin composition
JP1997227653A
Method for producing connected structure, anisotropic electroconductive bonding material, and connected structure
WO2021079812A1